Relationship between Emotional Intelligence and Organizational Performance in Nepalese Banks - K.C., Pradeep (Namuna Academic Journal, 2023)
The discourse over the issues concerning to Emotional Intelligence and organizational performance had and has presently been in interaction in various nations of the globe. The purposes of this paper are to assess the status of EI and OP in Nepalese Banks and to analyze the relationship between EI and OP. The research approach is quantitative, research design is descriptive and analytical too, and population is 47 Nepalese Commercial and development Banks. Structured questionnaire was designed to collect primary data through convenience sampling technique with five-point Likert scale. SPSS was used to manage and analyze data. Mean and Standard Deviations are used to assess the status of EI and OP, Pearson Correlation Matrix and Linear Regression Analysis to test relations and level of significance between variables, Chronbatch alpha to test reliability of constructs,. The research is able to find out that both EI and OP are well present in the Nepalese banking. This research paper shows that an employee with high EI has a high OP. Most of the constructs of EI have a significant relationship with OP.